Five Year Plan 1980-85 and Annual Plan 1981-82 Draft Proposals Volume I - Planning Commission (Planning Commission, 1981)
Meghalaya came into existence first as an Autonomous State within the State of Assam on April 2, 1970 and attained the full State-hood on January 21, 1972. It was formed initially with two hills districts, namely the United Khasi and Jaintia Hills and the Garo Hills, carved out of the Stale of Assam. It has now five administrative districts. Area and Population Meghalaya covers a land surface of 22,500 square kilometres approximately which is 0'70 per cent of the total area of India. Only four other States of India, namely Sikkim, Tripura, Nagaland and Manipur arc smaller than Meghalaya in area.
Planning Department